KONTRIBUSI DUKUNGAN ORANG TUA DAN MINAT BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SMP - Rianita Simamora; Yanty Maria Rosmauli Marbun (Universitas Islam Sumatera Utara, 2022)
The aims of this study were: (1) to determine the contribution of parental support to the mathematics learning achievement of eighth grade students of SMP YPAK PTPN III Gunung Para; (2) knowing the contribution of interest in learning to mathematics learning achievement of class VIII SMP YPAK PTPN III Gunung Para; (3) Knowing the magnitude of the contribution of the joint relationship between parental support and interest in learning on mathematics learning achievement for class VIII SMP YPAK PTPN III Gunung Para. This type of research is a correlational research with a quantitative approach, because in this study the relationship between parental support and interest in learning will be sought for learning achievement in mathematics. The correlation technique used is multiple correlation (multivariate) which is to determine the relationship between two independent variables together or more with one dependent variable.The population in this study was class VIII SMP YPAK PTPN III Gunung Para as many as 155 students divided into four parallel classes. The sampling technique used in this study is the Simple Random Sampling technique, so that the researcher determines the students of class VIII-3 with 39 students as the sample.This study uses a questionnaire type instrument and documentation. The questionnaire instrument used has met the validation requirements, totaling 27 statements each to obtain information from the three variables. To find out the first and second objectives in this study, the product moment correlation test and t test were used to see the significance of the relationship between variables. Meanwhile, to find out the third objective using multiple correlation test.The data that has been collected and analyzed shows that the contribution given by parental support and interest in learning to student achievement shows a fairly large number. The contribution of interest in learning to learning achievement is the largest (44.36%) when compared to the contribution given by parental support to learning achievement (28.09%). However, if parental support and interest together affect learning achievement, the contribution will increase to 46.40%.